Efektivitas Pelaksanaan Pembelajaran Tematik Masa Pandemi Covid 19 - Yamti Yamti; Kanthi Pamungkas Sari; Irham Nugroho (MODELING: Jurnal Program Studi PGMI, 2022)
Every school must use distance learning (PJJ) during the COVID-19 epidemic since face-to-face instruction will no longer be available to ensure that learning is maintained. There are challenges in its application, including limited internet connection and the use of technology for education. The research seeks to characterize the thematic learning implementation process, determine the effectiveness of the thematic learning implementation, and develop strategies to get around barriers to thematic learning implementation during the COVID 19 pandemic. The study employs a variety of mixed methods (qualitative and quantitative). The study's findings are as follows: first, because it meets the anticipated indicators, the process of adopting theme learning from planning through implementation and evaluation has gone successfully. Second, the success of thematic learning implementation through questionnaire distribution yielded 78.31 results in the good group. Thematic learning is being implemented throughout the COVID-19 epidemic successfully.